From the center: feminist essays on women's art - Lippard, Lucy R. (Dutton paperback original, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis